Inventory of aquatic macrophyte species in coastal rivers of the sÃo paulo state, Brazil - Nunes, Laís Samira Correia [UNESP]; Umetsu, Cristiane Akemi [UNESP]; Rodrigues, Maria Estefânia Fernandes; Pott, Vali Joana; Camargo, Antonio Fernando Monteiro [UNESP] (Oecologia Australis, 2019)
The coastal region of the São Paulo state (Southeastern Brazil) is marked by the presence of the Serra do Mar, a system of mountain ranges with altitude up to 1,000 m. Due to the difference of proximity of the mountain range to the coastline, the coastal plains have different width. As a consequence, the rivers that cross the plains also have different length, greater or less influence of marine waters and slope variation. We carried on an inventory of aquatic macrophyte species in order to assess the species and life form richness and latitudinal distribution in this region. Macrophytes were inventoried at 100 sampling sites in eight rivers (between 9 and 19 sites per river) in March 2017. General descriptions on taxonomic aspects, life forms and frequency of occurrence of the macrophytes were explored. We recorded 45 taxa of aquatic macrophytes belonging to 24 families. Three species are exotic, but they presented low frequencies of occurrence. The vast majority of the taxa have emergent life form. Floating and submerged macrophytes were found in only two rivers. The most frequent species were Crinum americanum L. (Asparagales, Amaryllidaceae), Spartina alterniflora Loisel. (Poales, Poaceae) and Schoenoplectus californicus (C. A. Mey.) Soják (Poales, Cyperaceae). Most taxa are rare in terms of occurrence. Only four species occurred along a large part of the north-south stretch sampled and these, possibly, have a wide tolerance to the variation in resource requirements and salinity. The north-south gradient of the taxa occurrence may be related to the diversity of environmental characteristics due to differences in the rivers length and coastal plains width.
Keywords: Aquatic plants; Coastal river basin; Estuary; Life forms